MENINGKATKAN KEMAMPUAN BERHITUNG AWAL MELALUI PERMAINAN CONGKLAK DI TK AZ-ZAHRA DESA TERAPU KECAMATAN ALUH-ALUH - Ahmad Saidi; Baiti , Noor; yusuf , Muhammad; Nisa, Uswatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine and describe the implementation of the congklak game in enhancing early numeracy skills at Az-Zahra Kindergarten, Terapu Village. This study employed Classroom Action Research (CAR) conducted with a group of 10 children (Group A) at Az-Zahra Kindergarten, Terapu Village. The research was carried out over two cycles comprising four meetings, covering four stages: planning, implementation, observation, and reflection. The results indicate that the use of the congklak game (dakuan/bedakuan) as a learning medium consistently and significantly improved the early numeracy skills of children aged 4–5 years at Az-Zahra Kindergarten across each cycle. Teacher activity improved from the "Adequate" category (62.50%) in Cycle I, Meeting 1, to the "Very Good" category (95.45%) in Cycle II, Meeting 2; meanwhile, child activity increased from the "Less Active" category (49.76%) to the "Very Active" category (85.36%) by the end of the study. Concurrently, the children's learning mastery regarding early numeracy skills increased gradually: from 20% in Cycle I, Meeting 1, to 40% in Cycle I, Meeting 2; then to 70% in Cycle II, Meeting 1; and finally reaching 100% in Cycle II, Meeting 2. At this final stage, 7 children (70%) were in the "Developing Very Well" (BSB) category and 3 children (30%) were in the "Developing as Expected" (BSH) category, with no children remaining in the "Beginning to Develop" or "Not Yet Developing" categories. Thus, the congklak game—as a learning medium based on Banjar local wisdom—proved effective in enhancing the early numeracy skills of young children at Az-Zahra Kindergarten, Terapu Village.